Three-dimensional piezoelectric fibrous scaffolds selectively promote mesenchymal stem cell differentiation. (December 2017) - Damaraju, Sita M.; Shen, Yueyang; Elele, Ezinwa; Khusid, Boris; Eshghinejad, Ahmad; Li, Jiangyu; Jaffe, Michael; Arinzeh, Treena Livingston
Abstract: The discovery of electric fields in biological tissues has led to efforts in developing technologies utilizing electrical stimulation for therapeutic applications. Native tissues, such as cartilage and bone, exhibit piezoelectric behavior, wherein electrical activity can be generated due to mechanical deformation. Yet, the use of piezoelectric materials have largely been unexplored as a potential strategy in tissue engineering, wherein a piezoelectric biomaterial acts as a scaffold to promote cell behavior and the formation of large tissues. Here we show, for the first time, that piezoelectric materials can be fabricated into flexible, three-dimensional fibrous scaffolds and can be used to stimulate human mesenchymal stem cell differentiation and corresponding extracellular matrix/tissue formation in physiological loading conditions. Piezoelectric scaffolds that exhibit low voltage output, or streaming potential, promoted chondrogenic differentiation and piezoelectric scaffolds with a high voltage output promoted osteogenic differentiation. Electromechanical stimulus promoted greater differentiation than mechanical loading alone. Results demonstrate the additive effect of electromechanical stimulus on stem cell differentiation, which is an important design consideration for tissue engineering scaffolds. Piezoelectric, smart materials are attractive as scaffolds for regenerative medicine strategies due to their inherent electrical properties without the need for external power sources for electrical stimulation.